Freedom of information in Scotland in practice - Dunion, Kevin (Dundee : Dundee University Press, 2011)
This is the only in-depth guide to Scotland's freedom of information (FOI) regime. Written by the first Scottish Information Commissioner, it provides detailed commentary on the provisions of the Freedom of Information (Scotland) Regulations 2004. It is fully referenced, using the Commissioner's own decisions and court judgements and provides a unique insight into the Commissioner's role in determining appeals and ensuring adherence to the Code of Practice.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Scotland; Government information -- Law and legislation -- Scotland; Government information -- Access control -- Scotland; Freedom of information -- Scotland; Law; Laws of specific jurisdictions & specific areas of law